Al-Ghazali In Literature With Special Reference To His Biography And The Issue Of Faith And Good Deeds - Mohd Rosmizi Abd Rahman (Universiti Sains Islam Malaysia, 2024)
This study offers a brief analysis on some biographical works on Imam al-Ghazali and his view on the issue of faith and good deeds through examination of various relevant literature. Imam al-Ghazali has been regarded as one of the world’s most influential thinkers as well as the greatest scholar Islam has ever produced. The life, teaching and thought of al-Ghazali have attracted the attention of many scholars, both Western and non-Western. The influence of al-Ghazali is not limited within his own tradition, but is felt both in the East and the West, reaching Jewish and Christian traditions. This study is theoretical in nature, and it involves bibliographic/library research. It surveys and offers a brief analysis of some literatures—mostly in English—that are relevant to al-Ghazali’s biography and his view on the issue of faith and good deeds. This study found that although there are some critical assessments and misunderstandings of al-Ghazali’s life and views, majority of literature consulted acknowledge his great scholarship and contributions in many aspects. Al-Ghazali did not remain indifferent but indeed ardently refuted the various interpretations related to the issue of good deeds which he considered as heretical. The research also shows that not only al-Ghazali always emphasised the observance of religious commandments, but he also breathed spirituality and gave deeper content and insight into the religious life.